A gestão da parceria/supervisão técnica em serviço socioassistencial contratado na cidade de São Paulo - Rocha, Estefani Clementino da (2018)
The presence of contractual provision of social assistance services with Civil Society Organizations (CSO) is no exception in Brazilian public management. Since the 1930s, this type of articulation has been adopted, although at the beginning more focused on transfers of financial resources through subsidies and exemptions. The contractualized format of social service management, even though it was nominated as an agreement, had its practice started in the 1960s and was disseminated to countless services and projects of Brazilian public social policy in the three federative entities. To such a point, the dissemination of this management format was denounced, due to its intransparency and lack of social control that flowed into a national audit, from which a new regulatory law flowed: the Regulatory Framework of State- Organizations Relation of Civil Society (MROSC). Thus, this study deals with the examination of the guarantees of social rights that the social assistance services contracted with the CSO, which operate in the Unified Social Assistance System (SUAS), assure their users, in order to highlight and problematize the practice of monitoring the service contracted, performed by the public agent, named by the new MROSC legislation as Manager of the Partnership, or by previous standards as Technical Supervisor, particularizing the management of SUAS in the city of São Paulo. Thus, the study was dedicated to identifying the ways in which the Manager / Technical Supervisor of social assistance services contracted in the city of São Paulo performed their professional work, as well as their main lines of action, through the analysis of normative acts published by the Municipal Secretary of Assistance and Social Development (SMADS). It is concluded that the practice of Partnership Management / Technical Supervision is weak in the city of São Paulo, in view of normative stimuli that direct its professional work, mainly for a centralizing management, with content of work front demarcated by the excess production of as well as by the strong imbalance in the constitution of the social assistance network, the accumulation of functions and power attributed to some CSO that hold the largest number of contracts with the São Paulo management of SUAS. However, despite this weakening, its action may occur within the regulations already built within the scope of the SUAS that consider the monitoring of the public agent as an instrument or mediation with power to articulate the content of the social assistance service contracted with the rights of users.